2022
DOI: 10.21123/bsj.2022.6422
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous Ratio Derivative Spectrophotometric Determination of Paracetamol, Caffeine and Ibuprofen in Their Ternary Form

Abstract: A new, accurate, precise and economic two spectrophotometric methods for determination of Paracetamol (Par), Ibuprofen (Ibu), and Caffeine (Caf) were suggested. Those methods were the first and second ratio derivative spectrum using a double devisor. Par, Ibu, and Caf showed many useful peaks for their quantified determination. The validity of all analysis modes for determination of the three compounds, peak to baseline, peak area and peak to peak were according to ICH. The linearity of two methods was between… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 22 publications
0
9
0
1
Order By: Relevance
“…Upon light absorption, an π electron is excited from the ground state to the first excited state, and new absorption peaks of the formed complex (Para-M(II)) ions have been attributed to the d→d transition (17), as shown in (Table 2 and Figure 4).…”
Section: Para-metal Complexesmentioning
confidence: 97%
See 2 more Smart Citations
“…Upon light absorption, an π electron is excited from the ground state to the first excited state, and new absorption peaks of the formed complex (Para-M(II)) ions have been attributed to the d→d transition (17), as shown in (Table 2 and Figure 4).…”
Section: Para-metal Complexesmentioning
confidence: 97%
“…Job's method of continuous variation (20,21), which is straightforward, quick, measurable, and valid, was employed to ascertain the stoichiometry and formation constants of Para-metal(ll) complexes by spectrophotometry. Metals and Para were mixed in various ratios ranging from 0.188:1 to 1:0.188, and the absorbance of each mixture was measured at the complexes' maxima (17,21).…”
Section: Para-metal Complexesmentioning
confidence: 99%
See 1 more Smart Citation
“…Alsamarrai and S.T. Ameen [20] used derivative spectrophotometry for the simultaneous determination of Paracetamol, Caffeine, and Ibuprofen in their ternary mixture. In these investigations, the authors were able to analyze the mixtures with high overlapping absorption spectra without the need for the prior separation of the species.…”
Section: Introductionmentioning
confidence: 99%
“…It is essentially obtained from coffee beans and leaves (Musa Ali et al, 2012), and also it can be found in tea leaves (Soni, 2019), cocoa beans (Grassia et al, 2019), and kola-nut (Umeda et al, 2020). This alkaloid is the most valuable, and its value comes from its importance to humans, where it works as a stimulant drug that improves attention (van Dam et al 2020) (Alsamarrai, 2022). However, the importance of caffeine as a pharmaceutical compound goes beyond just being a stimulant drug (Monteiro et al, 2019), where its effectiveness as a drug was studied for many medical cases to reduce their intensity or their possibility of accruing, such as consuming coffee may stimulate the gallbladder, which will reduce the risk of gallstones (Grosso et al, 2017).…”
Section: Introductionmentioning
confidence: 99%